2020
DOI: 10.3390/electronics9091456
|View full text |Cite
|
Sign up to set email alerts
|

Affordable and Faster Transradial Prosthetic Socket Production Using Photogrammetry and 3D Printing

Abstract: This study aims to invent a new, low-cost, and faster method of prosthetic socket fabrication, especially in Indonesia. In this paper, the photogrammetry with the 3D printing method is introduced as the new applicative way for transradial prosthetic making. Photogrammetry is used to retrieve a 3D model of the amputated hand stump using a digital camera. A digital camera is used for photogrammetry technique and the resulting 3D model is printed using a circular 3D printer with Polylactic acid (PLA) material. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 25 publications
0
12
0
1
Order By: Relevance
“…We developed a novel, universal 3D-printed socket that rapidly provides myoelectric control to individuals with transradial amputation in research settings. The 3D-printed fabrication approach has shown to be an appropriate short-term alternative to conventional techniques, offering high functionality at a small fraction of the time and cost of traditional socket-fabrication methods (Hallworth et al, 2020;Ismail et al, 2020). Our socket can be fabricated in ∼7 h at any time prior to participant arrival, custom fit within 10 mins, and donned in under a minute.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We developed a novel, universal 3D-printed socket that rapidly provides myoelectric control to individuals with transradial amputation in research settings. The 3D-printed fabrication approach has shown to be an appropriate short-term alternative to conventional techniques, offering high functionality at a small fraction of the time and cost of traditional socket-fabrication methods (Hallworth et al, 2020;Ismail et al, 2020). Our socket can be fabricated in ∼7 h at any time prior to participant arrival, custom fit within 10 mins, and donned in under a minute.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the socket must be manufactured at a low cost, utilizing common manufacturing and printing materials, to ensure accessibility. Conventional transradial sockets intended for long-term use range from $800 to $3,000 USD (Limb Prostheses (Conventional) Product Manual, 2012;Frossard et al, 2017), with recently developed low-cost alternatives ranging from $100 to $200 USD-the cost of which may still be prohibitively high-making the desired cost under $100 USD (Alkhatib et al, 2019;Ismail et al, 2020;Miller et al, 2020). A device intended for short-term research could feasibly be even more economical still.…”
Section: Criteria Accessibilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Photogrammetry is a digitisation technique in which a collection of 2D photographs from different viewpoints of an object are analysed with specialised software. Key elements are identified that can be seen in multiple images, allowing points to be located in a 3D space relative to each other, forming a 3D surface mesh [19][20][21].…”
Section: Introductionmentioning
confidence: 99%